2015
DOI: 10.3390/ijms16011179
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Splicing Improvement by the Combined Application of Antisense Strategies

Abstract: Spliceosome-mediated RNA trans-splicing has become an emergent tool for the repair of mutated pre-mRNAs in the treatment of genetic diseases. RNA trans-splicing molecules (RTMs) are designed to induce a specific trans-splicing reaction via a binding domain for a respective target pre-mRNA region. A previously established reporter-based screening system allows us to analyze the impact of various factors on the RTM trans-splicing efficiency in vitro. Using this system, we are further able to investigate the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…First, a pool of highly variable binding domains (BD) was generated through amplifying the COL7A1 gene region spanning from intron 75 to exon 80 and subsequent fragmentation via sonification. The resulting BD fragments ranging from 50 to 300 nucleotides were cloned into a previously described 3′ RTM screening vector [16,17,22] (Figure 1A). In total, 24 3′ RTMs with BDs in antisense orientation to the COL7A1 target region intron 75–exon 80 were included in co-transfection studies in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, a pool of highly variable binding domains (BD) was generated through amplifying the COL7A1 gene region spanning from intron 75 to exon 80 and subsequent fragmentation via sonification. The resulting BD fragments ranging from 50 to 300 nucleotides were cloned into a previously described 3′ RTM screening vector [16,17,22] (Figure 1A). In total, 24 3′ RTMs with BDs in antisense orientation to the COL7A1 target region intron 75–exon 80 were included in co-transfection studies in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The stable COL7A1 -dTS-MG expressing cell line was created according to a previously published protocol [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various experiments have shown that minor variations in length, sequence or localization of the target-binding position influence the splicing characteristics of a given RTM. 20, 21, 22, 40 The rational design of RTMs is difficult since up to now only few guidelines for generating potential RTMs exist. Consequently, we have recently developed an RTM reporter-based screening system that accelerates and facilitates RTM construction for any target pre-mRNA region of choice in a co-transfection assay.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of using SMaRT to reprogram mRNA is the correction of the Tau isoform imbalance that is characteristic of FTDP-17 and tauopathies [67,68,69]. Recently, the trans -splicing system has been optimized through the combination of the trans-splicing RNA and antisense RNA interfering with competitive splicing elements on the pre-mRNA [70,71]. A comprehensive review detailing the use of SMaRT in gene therapy for genetic diseases has been recently published [63].…”
Section: Therapeutic Approachesmentioning
confidence: 99%